Research in organizational change and development. Vol. 12 - Pasmore, William A.; Woodman, Richard W. (Research in organizational change and development,, 2000)
Ideas which are comfortable and familiar are not likely to challenge or transform our thinking. As human beings, our need to reduce cognitive dissonance causes us to seek the familiar and reject the unfamiliar, often without careful reflection. Scholars must overcome such natural tendencies in order to look beyond the reaches of well accepted doctrine, exploring less-understood and less-accepted explanations of the way things are, and consider instead the possibilities that alternative futures could hold. Collectively the chapters that make up volume 12 are a statement of the vibrancy and ever changing nature of the field of organizational change and development.